Comparison between Hypertensive and Non-Hypertensive Individuals in the Value of Response to Salt Administration (Medico Legal Update, 2020)
Background: consumption of,salt (sodium-chloride) causes,increment of blood pressure (B.P) in both normal and,hypertensive individuals, that is why,the use of diuretics which eliminate salts from the body decreases the B.P. and used as a line of treatment,in hypertension.Objective: the study,aims to know whether there is any,difference in the increment of B.P. both systolic and diastolic between normal people and hypertensive people after giving salt orally.Method: one hundred individuals were involved in the study, 50 patients were hypertensive,individuals (25 males and 25 females) and labelled as group A, and 50 persons (25 males and 25 females) were normal individuals and labelled as group B and played as control. After full physical examination including 3 times B.P. checking before and after giving 6 gm of sodium-chloride (table salt) orally ; after 2 hours the values of B.P. were recorded and statistical,analysis was done to know the difference,between the two groups.Results: in all individuals of both groups, the B.P. increased,after salt consumption. In group A (the hypertensive group) the mean increment,of systolic B.P. (S.B.P.) was (15.98) mmHg and the mean diastolic B.P. increment (D.B.P.) was (9.4) mmHg , while the mean S.B.P. increment,in group B was (8.7) mmHg and mean D.B.P. increment was (8.0) mmHg.Conclusion: the study showed significant difference in the increment of B.P., both systolic and diastolic between the two groups, showing that hypertensive group is more sensitive to salt consumption than normal individuals (the control group).